2021
DOI: 10.34194/geusb.v45.5298
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-tectonic development of the Wandel Sea Basin, North Greenland

Abstract: The Carboniferous–Palaeogene Wandel Sea Basin of eastern North Greenland (north of 80°N, east of 40°W) is an important piece in the puzzle of Arctic geology. It is particularly important for understanding how the Paleocene–Eocene convergence between Greenland, the Canadian Arctic and Svalbard relates to the compressional tectonics in the High Arctic, collectively known as the Eurekan Orogeny. In this study, we present apatite fission-track analysis (AFTA) data and review published vitrinite reflectance data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 73 publications
1
15
1
Order By: Relevance
“…In North Greenland, we sampled two sites on Prinsesse Thyra Island, one site on Prinsesse Margrethe Island, and several locations at Nakkehoved, including specimens of the quartz veins (Figures 2a, Table S1 in Supporting Information S1). Unlike previous descriptions in the literature (e.g., Håkansson et al, 1994;Japsen et al, 2021), we found that quartz veins within the Nakkehoved Formation are not restricted to a single exposure but also occur in situ in another outcrop of the Nakkehoved Formation in Kronprins Christian Land (Figures 2a, Table S1 and Figure S1 in Supporting Information S1).…”
Section: Sampling Strategy Field Observations and Description Of The ...contrasting
confidence: 81%
See 4 more Smart Citations
“…In North Greenland, we sampled two sites on Prinsesse Thyra Island, one site on Prinsesse Margrethe Island, and several locations at Nakkehoved, including specimens of the quartz veins (Figures 2a, Table S1 in Supporting Information S1). Unlike previous descriptions in the literature (e.g., Håkansson et al, 1994;Japsen et al, 2021), we found that quartz veins within the Nakkehoved Formation are not restricted to a single exposure but also occur in situ in another outcrop of the Nakkehoved Formation in Kronprins Christian Land (Figures 2a, Table S1 and Figure S1 in Supporting Information S1).…”
Section: Sampling Strategy Field Observations and Description Of The ...contrasting
confidence: 81%
“…Japsen et al. (2021) found that the thickness of the Thyra Ø Formation at Kap Rigsdagen was less than 3 km based on VR and AFT data. The observed thermal maturity may hence simply be a result of burial without a thermal anomaly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations